IMPROVING EARLY CHILDHOOD COGNITIVE ABILITIES THROUGH HAND MOVEMENT METHOD - Ratna Lina Marliana; Nandang Rukanda; Sri Nurhayati (IKIP Siliwangi Bandung, 2021)
The purpose of this study was to examine how early childhood cognitive ability development occurs in case 1) Memory 2) Recognize numbers and their sequences, and 3) Application of educational materials in everyday life. The research method and approach are qualitative descriptive, with data collection instruments including observation sheets, interviews, attitude scale questionnaires, and documentation studies. Qualitative analysis was used to supplement descriptive statistical analysis. Ten individuals participated in the research, six (six) boys and four (four) girls from group B TKQ Mutiara Qolbu Cihampelas West Bandung Regency. The research revealed that: 1). The use of hand movement method can help children improve their memory. This is evident in the increasing amount of food and drink that the child recalls. Initially, the child could recall only three materials adab eating and drinking in two weeks. After two weeks, the child could recall six materials. 2) Children can recognize numbers and classify movements according to direction, whereas previously the child was restricted to knowing the numbers and the order of movement. 3) The child can recall previously taught material but has been unable to apply it in his daily life. The study's findings indicated that hand movement method was effective at improving early childhood cognitive abilities. This study suggests that when combined with learning media, repetition, and habituation at home with parents, hand movement method may be more effective. Along with being easily remembered, the material can also be applied optimally on a daily basis.Keywords: early childhood, hand movement method, cognitive abilitiesAbstrakPenelitian ini dilakukan dengan tujuan untuk melihat bagaimana perkembangan kemampuan kognitif anak usia dini dalam hal 1). Daya ingat, 2). Mengenal angka dan urutan, serta 3). Pengaplikasian materi dalam kehidupan sehari-hari. Metode dan pendekatan penelitian yang diambil adalah deskriptif kualitatif, di mana lembar observasi, wawancara, angket skala sikap, dan studi dokumentasi menjadi instrument dalam pengumpulan datanya. Data dianalisis secara kualitatif yang dilengkapi dengan analisis statistik deskriptif. Subjek penelitian berjumlah 10 (sepuluh) orang, yang terdiri atas 6 (enam) orang anak laki dan 4 (empat) orang anak perempuan di kelompok B TKQ Mutiara Qolbu Cihampelas Kabupaten Bandung Barat. Dari hasil analisis data ditemukan bahwa 1). Penggunaan metode gerakan tangan dapat meningkatkan daya ingat anak, hal ini dapat dilihat dari bertambahnya materi adab makan dan minum yang diingat anak. Yang asalnya anak hanya mampu mengingat 3 (tiga) materi adab makan dan minum dalam dua minggu menjadi 6 (enam) materi dalam dua minggu. 2) Anak dapat mengenal angka dan mengurutkan gerakan sesuai arahan, dimana pada awalnya anak masih terkendala dalam mengenal angka dan urutan gerakannya, 3) Anak dapat mengingatkan orang sekitar materi yang telah diajarkan, namun belum dapat mengaplikasikan materi tersebut dalam kehidupan sehari-harinya. Implikasi dari penelitian ditemukan bahwa metode gerakan tangan mampu mengembangkan kemampuan kognitif anak usia dini. Rekomendasi dari penelitian ini adalah metode gerakan tangan akan lebih efektif apabila disertai dengan media pembelajaran, dilakukan pengulangan, dan pembiasaan di rumah bersama orang tua, sehingga selain materi dapat diingat dengan baik, dapat juga diaplikasikan dalam kehidupan sehari-hari dengan optimal..Kata Kunci: Kemampuan kognitif, metode gerakan, anak usia dini